Matlandskap : om kommuners fysiska planering för hållbara livsmedelssystem - Wingård, Karolina (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2021)
Food production and land use could be blamed for a lot of the global environmental issues present in todays society. With an ever increasing global population and steadily increasing effects of climate change, which threaten our crops, there is likely potential for issues to increase in scope and severity. The challenge at hand lies in feeding a growing population without overtaxing our natural resources. Food is relatable and relevant to all of UN:s Sustainable Development Goals and in a sustainable food production context, that includes aspects of relations regarding that of man and nature, urban and rural areas, and production and consumption. Even if food concerns all of us, our relations to food production has in many ways been lost. A strenghening of those relations could mean an increased valuation of food, food production and by extension an increased valuation of our natural resources. Land usage planning and asociated responsibilities is in Sweden governed by the local municipalities, which in effect means that a lot of food production policies set on a regional, national and international level are interpreted and applied by the municipalities themselves. Each municipality has the opportunity to provide the best prerequisites for a resilient local community, and food has potential to be the tool used to reach that goal. To achieve good food connections and knowledge about what constitutes a sustainable food landscape on a local level, inventory of food production resources in the municipality can be a useful tool. The planning of a food landscape, or foodscape, challenges all sectorial compartmentalisation on all governing levels. Furthermore, foodscape can broaden practises of physical planning.